2009
DOI: 10.5194/acp-9-9329-2009
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone from IASI: comparison of different inversion algorithms and validation with ozone sondes in the northern middle latitudes

Abstract: Abstract. This paper presents a first statistical validation of tropospheric ozone products derived from measurements of the IASI satellite instrument. Since the end of 2006, IASI (Infrared Atmospheric Sounding Interferometer) aboard the polar orbiter Metop-A measures infrared spectra of the Earth's atmosphere in nadir geometry. This validation covers the northern mid-latitudes and the period from July 2007 to August 2008. Retrieval results from four different sources are presented: three are from scientific p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 35 publications
6
67
0
Order By: Relevance
“…A validation exercise performed on IASI using balloonsonde measurements indicated that total column measurements and the retrieval errors are less than 5%. This is consistent with the standard deviation difference between the ozonesondes and IASI data (Keim et al, 2009). More details on IASI instrument can be found in http://www.ospo.…”
Section: Infrared Atmospheric Sounding Interferometer (Iasi)supporting
confidence: 77%
See 1 more Smart Citation
“…A validation exercise performed on IASI using balloonsonde measurements indicated that total column measurements and the retrieval errors are less than 5%. This is consistent with the standard deviation difference between the ozonesondes and IASI data (Keim et al, 2009). More details on IASI instrument can be found in http://www.ospo.…”
Section: Infrared Atmospheric Sounding Interferometer (Iasi)supporting
confidence: 77%
“…OMI provides data to derive ozone as well as to measure cloud pressure and coverage. OMI has high spectral capability, which improves the level of precision and accuracy of ToZ (Keim et al, 2009). It uses a linear fit algorithm for the retrieval of ToZ.…”
Section: Ozone Monitoring Instrument (Omi)mentioning
confidence: 99%
“…Validation with and comparison to independent measurements of other IASI products have been performed Keim et al, 2009;Pittman et al, 2009;Viatte et al, 2011;Dufour et al, 2012;Pommier et al, 2012;Scannell et al, 2012;Gazeaux et al, 2013) and also comparison to models (Parrington et al, 2012). In general, these studies focus on the determination of the bias and the correlation with respect to independent measurements and on the determination of the information content.…”
Section: Existing Iasi Ozone Data Productsmentioning
confidence: 99%
“…In general, these studies focus on the determination of the bias and the correlation with respect to independent measurements and on the determination of the information content. Only Keim et al (2009) and Dufour et al (2012) also studied the precision of the retrievals.…”
Section: Existing Iasi Ozone Data Productsmentioning
confidence: 99%
“…In their work, Eremenko et al (2008) used ozone profiles retrieved with an analytical altitude-dependent regularization method from the Infrared Atmospheric Sounding Interferometer (IASI; Clerbaux et al, 2009) data. IASI ozone profiles have been thoroughly validated for example by Keim et al (2009) and Dufour et al (2012). In the second case study, we compared the operational and modified ozone profiles against ozonesonde data from North America for AugustSeptember 2006.…”
Section: Introductionmentioning
confidence: 99%